Update on central factors in myopia development beyond intraocular mechanisms - Tian, Rui-Kang; Tian, Xiao-Xue; Yang, Hai-Bo; Wu, Yi-Ping (Frontiers in Neurology, 2024)
Myopia, a prevalent refractive error, primarily affects children and adolescents, characterized by excessive axial elongation causing distant objects to focus in front of the retina. This review explores the intricate mechanisms beyond intraocular factors, emphasizing the significant role of central factors in myopia development and progression. Intraocular mechanisms involving the retina, RPE/choroid, and sclera are well documented, with these structures playing crucial roles in eye growth regulation. Central factors, including brain structure and function alterations, are increasingly recognized, supported by advanced imaging techniques such as fMRI and rs-fMRI. Clinical findings highlight changes in brain activity and connectivity in high myopia (HM), suggesting neural plasticity or compensatory mechanisms. Animal studies further elucidate central mechanisms, indicating the involvement of specific brain nuclei like the visual cortex and suprachiasmatic nucleus. Understanding these complex interactions between intraocular and central mechanisms is crucial for developing novel therapeutic strategies to inhibit myopia progression and prevent associated complications. This review aims to provide a comprehensive analysis of current research, contributing to a deeper understanding of central factors of myopia.